2007
DOI: 10.1016/j.jfca.2006.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide levels in cooked rice, tomato sauces and some fast food on the Italian market

Abstract: This study reports the results of evaluation of acrylamide levels in some foods that are common on the Italian market. Three foods commonly found in the national diet (rice, tomato sauce and fast food), were examined with the gas chromatograph (GC)/mass spectrometer (MS) analytical method. Results show that rice differs from risotto with respect to acrylamide levels: values of less than 50 mg/kg, for boiled rice, increase to 113 mg/kg when various ingredients are added to produce risotto. Similar results were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…A lot of studies confirmed the presence of acrylamide in nearly all fried, baked, and roasted foods sold in Germany (Gutsche et al 2002), UK (Ahn et al 2002), Sweden (Svensson et al 2003), Netherland (Konings et al 2003), Hon Kong (Leung et al 2003), Japan (Ono et al 2003), Austria (Murkovic 2004), Australia (Croft et al 2004), Turkey (Şenyuva and Gökmen 2005a), Spain (RufianHenares et al 2007), Finland (Eerola et al 2007), Italy (Tateo et al 2007), Brasil (Arisseto et al 2007), China (Zhang et al 2007), Korea (Koh 2007).…”
Section: Occurrence Of Acrylamide In Foodsmentioning
confidence: 97%
“…A lot of studies confirmed the presence of acrylamide in nearly all fried, baked, and roasted foods sold in Germany (Gutsche et al 2002), UK (Ahn et al 2002), Sweden (Svensson et al 2003), Netherland (Konings et al 2003), Hon Kong (Leung et al 2003), Japan (Ono et al 2003), Austria (Murkovic 2004), Australia (Croft et al 2004), Turkey (Şenyuva and Gökmen 2005a), Spain (RufianHenares et al 2007), Finland (Eerola et al 2007), Italy (Tateo et al 2007), Brasil (Arisseto et al 2007), China (Zhang et al 2007), Korea (Koh 2007).…”
Section: Occurrence Of Acrylamide In Foodsmentioning
confidence: 97%
“…Tareke et al [12] observed a similar phenomenon when they analyzed the acrylamide content in fried potatoes mixed with milk, egg, or flour, compared with fried potatoes without these additives. In comparable surveys, Tateo et al [15] reported an acrylamide content ranging from 50 to 159 μg/kg in Italy, while Eerola et al [16] measured values <68 μg/kg in Finnish foodstuffs. Paleologos and Kontominas [11] referred to an FDA [14] study according to which chicken nuggets, which are similar to the products they evaluated, contained minimal amounts of acrylamide, not exceeding 20-25 μg/kg and suggested that this contradiction may be partly attributed to the amount and composition of the batter, to differences in the heat process used, and to the diet of the chickens.…”
Section: Deep Fryingmentioning
confidence: 94%
“…This could be explained by the fact that onion contributes to AA formation. It was shown 38 that onion among other ingredients used for seasoning increased the AA content. Analysis of the AA content in the same type of food from the market (the same receipt and manufacturing process according to the producer declaration) with different batches showed differences in the AA content.…”
Section: Methods Applicationmentioning
confidence: 99%